Use of Risk Analysis in Computer-Aided Persuasion - Duman, Ekrem (IOS Press, 2014)
Defense systems, computer networks and financial systems are increasingly subject to attack by terrorists, fraudsters and saboteurs. New challenges require concerted action from researchers to develop successful designs for computer networks that are resilient to deliberate attacks, and capacities must be built into the network to allow for quick and automatic recovery with little or no interruption or loss. This book contains contributions to the NATO Advanced Research Workshop on The Use of Risk Analysis in Computer-Aided Persuasion held in Antalya, Turkey in May 2011. The goal has been to further the research and knowledge in the areas of combatting threats and risks to entities, systems, and networks. The papers presented here fall into three categories. The first deals with fraud and financial systems. The second one considers threats to security and economic entities. The third group of papers considers computer network, IT, and software threats. Cutting edge methods based on neural networks, social network analytics, Bayesian networks, decision trees, and risk hedging have been proposed in these works to deal with these challenging problems.